2016
DOI: 10.14800/rci.1323
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of receptor activator nuclear factor-kB (RANK) in denervation-induced muscle atrophy and dysfunction

Abstract: The bone remodeling and homeostasis are mainly controlled by the receptor-activator of nuclear factor kB (RANK), its ligand RANKL, and the soluble decoy receptor osteoprotegerin (OPG) pathway. While there is a strong association between osteoporosis and skeletal muscle dysfunction, the functional relevance of a particular biological pathway that synchronously regulates bone and skeletal muscle physiopathology remains elusive. Our recent article published in the American Journal of Physiology (Cell Physiology) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Currently, there are two potential factors that have been studied regarding the influence of denervation on SERCA function, one is through phospholamban (PLN) [ 28 ], and the other is via receptor activator nuclear factor-kB (RANK) [ 14 , 15 ]. As mentioned above, PLN is an inhibitor of SERCA pumps expressing in all muscle types.…”
Section: Age Related In Changes In Serca Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are two potential factors that have been studied regarding the influence of denervation on SERCA function, one is through phospholamban (PLN) [ 28 ], and the other is via receptor activator nuclear factor-kB (RANK) [ 14 , 15 ]. As mentioned above, PLN is an inhibitor of SERCA pumps expressing in all muscle types.…”
Section: Age Related In Changes In Serca Activitymentioning
confidence: 99%
“…Receptor-activator of nuclear factor-κB (RANK), its ligand RANKL, and the soluble decoy receptor osteoprotegerin (OPG) are members of the tumor necrosis factor superfamily that regulate bone remodeling [ 29 , 32 ]. The study of the regulating roles of Ca 2+ through the interactions between RANK and RANKL is still a newly emerging area, but its function related to regulating cellular Ca 2+ storage and a series of Ca 2+ pumps in denervated muscles has been measured [ 14 , 15 ]. In a muscle-specific RANK knock out mouse model, they demonstrated that in denervated fast twitch muscles (EDL), the RANK deletion markedly increased the content of STIM 1, a Ca 2+ sensor, the SERCA activity, the SR Ca 2+ storage, and also the corresponding muscular functions, such as force production and muscle fatigability [ 15 ].…”
Section: Age Related In Changes In Serca Activitymentioning
confidence: 99%
“…This may be explained by the function of denosumab, which prevents binding of the RANK receptor by RANKL, with a resultant reduction in cytokines (e.g., TNF can cause muscle wasting and cellular apoptosis). Prior to this, some researchers confirmed that conditional knockout of RANK in muscle could prevent denervation-induced muscle weakness ( Dufresne et al, 2016a ). Taken together, the RANK/RANKL/OPG system may play an important role in muscle metabolism and the development of sarcopenia.…”
Section: Bone-muscle Biochemical Crosstalkmentioning
confidence: 99%